Long Non-Coding RNA SNHG3 Promotes the Progression of Cholangiocarcinoma by Regulating the miR-151a-3p/STAT5a Axis - Wei, Xiaoping; Cun, Dongyun; Yang, Danping; Yi, Qianyao; Tian, Daguang (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Studies have shown the significance of long non-coding RNAs (lncRNAs) in the development of malignant tumors, including cholangiocarcinoma (CCA). However, the molecular mechanisms through which the lncRNA SNHG3 contributes to CCA development remain unknown. Therefore, the purpose of this work was to investigate SNHG3’s role and possible processes in CCA. Materials and Methods: CCK-8, TUNEL, wound healing, and transwell assays were performed to evaluate the viability, apoptosis, migration, and invasion of CCA cells, respectively. Dual-luciferase reporter and RNA pull-down assays were conducted to verify the relationship between SNHG3 and miR-151a-3p and that between STAT5a and miR-151a-3p. Results: SNHG3 and STAT5a were considerably upregulated and miR-151a-3p was downregulated in CCA tissues and cells. SNHG3 knockdown suppressed the proliferation, apoptosis, migration, and invasive ability of HUCC-T1 cells. Mechanistically, SNHG3 directly targeted miR-151a-3p to promote the development of CCA. Treatment with a miR-151a-3p inhibitor reversed the effects of SNHG3 knockdown on the aggressive behavior of HUCC-T1 cells. Furthermore, STAT5a knockdown counteracted the effects of inhibition of SNHG3 and miR-151a-3p on the aggressive behavior of CAA. Conclusion: SNHG3 promotes CCA progression via the miR-151a-3p/STAT5a axis, providing novel insights into the clinical treatment of CCA. Cite this article as: Wei X, Cun D, Yang D, Yi Q, Tian D. LncRNA SNHG3 promotes the progression of cholangiocarcinoma by regulating the miR-151a-3p/STAT5a axis. Turk J Gastroenterol. 2024;35(12):933-944.